Kajian Teknis dan Ekonomi Pembangkit Listrik Tenaga Sampah (PLTSa) Menggunakan Perangkat Lunak LandGEM TPA Kebon Kongok Gerung Lombok Barat - Muljono, Agung Budi; Mukti, Komang Bagus Khrina; Natsir, Abdul (DIELEKTRIKA, 2022)
Energy use currently still depends on the use of fossil energy, especially in Indonesia, the use of fossil energy is still the main source of energy. The utilization of urban waste is one of the national priorities in the field of new and renewable energy, this is also the background for making waste an object of research in the conversion of electrical energy. This final project will create a waste power plant located in the city of Mataram. The potential study is based on the amount of waste contained in the Kebon Kongok landfill. The parameters used in the feasibility analysis of a solid waste power plant are Net Present Value (NPV), Benefit-Cost Ratio (BCR), Payback Period (PP), and Internal Rate of Return (IRR). The results showed that the Kebon Kongok landfill has a potential production of Landfill Gas (LFG) of 7,100,769,959 m3 per year. The electrical energy that can be sold to PT PLN (Persero) is 64,226,464.28 kWh per year. Based on the calculation of the investment cost needed to realize a solid waste power plant in Mataram city of Rp. 997,779,793,920,-, (NPV) = Rp. 435.227.788.872.53,-, PP = 7.6 years, BCR = 1.33, and IRR = 4.27%. This means that the waste power plant is feasible to be realized.